INDICADORES DE RENTABILIDADE DA PRODUÇÃO LEITEIRA NUMA PROPRIEDADE NO MUNICÍPIO DE AQUIDAUANA/MS - SANTOS, M. G. R.; PANDOLFO, J.; VEIGA, P. T. N.; FERREIRA, R. C.; OLIVEIRA, M. V. M.; SABBAG, O. J. (ANAIS DO ENIC, 2016)
-